Learning environment in remote education – from own practice of an academic teacher - Krzeczkowska, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The article elaborates on some topics about an environment of teaching and learning process. It contains the discussion focusing on the teachers’ personal reflections about it as a crucial element of teachers’ preparation for on-line students’ meetings. The presented author’s reflections are based on her own observations during the course “Basic chemistry”. How to transfer knowledge through the computer screen in the absence of direct exchange of signals between the teacher and the student? Do we know how to avoid fatigue and distraction of our students during remote classes? Is it necessary to select the content for those that must be carried out in the classroom? Is it possible to build relationships remotely? Are the rules of online work, savoir-vivre in online classes necessary?